The Association Between Oral Lichen Planus and HCV Infection - Javed A Qazi; Abdul Haseeb Qazi (Journal of the Dow University of Health Sciences, 2011)
Objective: The purpose of this study was to investigate the possible epidemiological relationship between Oral Lichen Planus (OLP) and Hepatitis C Virus (HCV) infection in Peshawar.